The suffering measurement instruments in palliative care: A systematic review of psychometric. - Gutiérrez-Sánchez, Daniel; Gómez García, Rafael; Cuesta-Vargas, Antonio; Pérez-Cruzado, David Francisco (Elsevier, 2020)
The relief of suffering is considered one of the main goals to reach at the end of life, and nurses play an essential role in the prevention and relief of suffering. Validated instruments for assessing suffering can be useful, and selection of the most appropriate measure is crucial. To date, no systematic review has been performed that contrasts the measurement properties of instruments assessing suffering in the palliative care population, according to the most up-to-date COnsensus-based Standards for the selection of health status Measurement INstruments methodology. Objectives The aim of this systematic review is twofold: (1) identify the measures assessing suffering in the palliative care population, and (2) assess the measurement properties of these measures. Results The search strategy yielded a total of nine studies and six instruments assessing suffering. The methodological quality of the studies was doubtful and the quality of the evidence was moderate for most of the measurement properties analysed. The Suffering Pictogram was the instrument with the best rating for methodological quality and quality of evidence, for most of the measurement properties evaluated. Conclusions Instruments assessing suffering in palliative care have been identified in this systematic review. The Suffering Pictogram seems to be the most useful instrument identified. Tweetable abstract: The relief of suffering is one of the main goals to reach at the end of life, and the selection of the most appropriate measure for assessing this construct is crucial.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/4633
Keywords: Cuidados terminales - Aspectos psicológicos; Nursing assessment; Surveys and questionnaires; Systematic review; Validation studies; Reproducibility of results; Palliative care